(untitled) (Scientific journal of the Fergana State University, 2023)
Winged words have a great role in the national and world culture. They are the words of great philosophers, scientists, writers and statesmen. They are the word combinations which make our speech more meaningful and bright. This article deals with the concept of winged words and their differences from quotations that serve to express succinctly various character traits and situations in figurative expressions.